Equação do calor: soluções analítica numérica - LEAL, Camila Rodrigues e Rodrigues (2023)
This work contains an introduction to differential equations, where the main objective is to present solutions for the heat equation. A detailed study was made of the method of separation of variables applied to the problem of the heat equation; in usual terms, this method consists of separating the terms involving the partial derivatives by the equal sign, so that the EDP present in the heat conduction is solved. To have a good understanding, we discuss some concepts and definitions to develop the finite difference solution method, using computer numerical simulations with a focus on the parabolic equation of heat.